2021
DOI: 10.5114/areh.2021.106027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise training on leptin and liver enzymes in non-diabetic overweight hepatitis C men

Abstract: Introduction: Leptin is one of the new adipokines that reflects the pathological status of liver tissue in the chronic hepatitis C virus (HCV). This study aimed to investigate the leptin and liver enzymes responses to aerobic exercise (AE) in overweight nondiabetics with HCV.Material and methods: Forty nondiabetic non-cirrhotic HCV men aged 40-60 years old with a body mass index (BMI) varied from 25-29.9 kg/m2 were divided randomly to study and control groups. The study group (n = 20) received a 3-session cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The suggested mechanisms that explain the improvement in MeTS components in this CPP study reduction may be reported as follows: reduction in overactivity of the sympathetic nervous system; improvement in elastic and endothelial properties/functions of vessels; enhancement functions of micro- and macrocirculation; increased production of vasodilating substances such as nitric oxide (NO), reduced production of plasma vasoconstrictors/catecholamines [ 17 ]; improved insulin resistance (may be due to repeated contraction of large muscles of lower limbs that increase the transportation, phosphorylation, and oxidization of glucose molecules during walking) [ 5 ]; and increased activity of lipolytic enzymes that catabolize STG [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The suggested mechanisms that explain the improvement in MeTS components in this CPP study reduction may be reported as follows: reduction in overactivity of the sympathetic nervous system; improvement in elastic and endothelial properties/functions of vessels; enhancement functions of micro- and macrocirculation; increased production of vasodilating substances such as nitric oxide (NO), reduced production of plasma vasoconstrictors/catecholamines [ 17 ]; improved insulin resistance (may be due to repeated contraction of large muscles of lower limbs that increase the transportation, phosphorylation, and oxidization of glucose molecules during walking) [ 5 ]; and increased activity of lipolytic enzymes that catabolize STG [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exercises done using the ankle weights included seated knee flexion and extension and standing knee flexion and extension [16]. These exercises were chosen because the strength of the muscles has an effect on stability, mobility, function, and QoL [17,18]. Exercises were done 3 times per week for 30 minutes in each session.…”
Section: Group 2: Exercisesmentioning
confidence: 99%
“…3 After that, Mahmoud A and others also mentioned this term in their respective published articles, but they are only a superficial explanation, there is no research on its definition and its composition. 4 The earliest expression of the concept of "special ability" was put forward by Rezaei S in 1999: Special ability refers to the competitive ability an athlete has in a specific special field, and it is the competitive ability that must be possessed to improve the level of special training and the performance of special sports. Therefore, it is a subordinate concept of athletic ability and a part of athletic ability.…”
Section: Introductionmentioning
confidence: 99%